Study of processing of watermelon jam enriched with jabuticaba extracts and chia seed extract: physico-chemical characteristics and antioxidant potential (Research, Society and Development, 2020)
The objective of this work was to develop watermelon jelly with three jabuticaba extracts and chia seed extract (to replace part of the pectin) in order to study the antioxidant capacity of the products, before and after thermal processing, as well as the determination of the physicochemical characteristics of the products obtained. Experimental plans were made for the development of the products, using the program Statsoft Statistica and to express the results in mean ± standard deviation, the software Sisvar 5.6. Four jellies were elaborated: watermelon jelly; jelly enriched with Jabuticaba I extract - bark and seeds (Jelly I); jabuticaba II extract - unfiltered pulp (Jelly II) and jabuticaba III extract - filtered pulp (Jelly III). The last three with chia extract partially replacing pectin. The analyses performed on these products consisted of proximal composition, pH analysis, soluble solids, acidity, water activity, colorimetric analysis and analysis of antioxidant capacity before and after processing (DPPH method, ABTS and FRAP). The current legislation does not specify parameters for physical-chemical analysis. Losses of its antioxidant capacity were observed in the three methods, with significant loss for watermelon jelly with 45 and 40%, respectively in the DPPH and ABTS methods and loss of 23.5 to 40% in enriched jellies, by the DPPH method. There was no significant difference for losses in the ABTS and FRAP tests, which did not exceed 10.5% for enriched jellies. It is concluded that enriched jellies lost non-relevant amounts of antioxidant compounds, highlighting the positive effect of inserting the extracts. In addition, chia extract contributed positively to the formation of the gel and extract 1 (peels and seeds) contributed notably to the enrichment of jelly I, about 309 times more than in watermelon jelly, confirming the hypothesis planted in our objectives. We suggest further research on the influence of parameters such as time and temperature and in vitro methods on bioactive compounds with antioxidant capacity.